CYSTIC DUPLICATION OF THE STOMACH IN CHILDREN - Sattarov Zh.B.; Boboev M.Sh. (Web of Journals Publishing, 2025)
A 1-year-old patient was hospitalized for further examination of a cystic formation in the abdominal cavity, detected in the child at the age of 6-7 months. After that, the patient underwent CT of the abdominal cavity and retroperitoneal space, which determined a cystic formation in the area of the adrenal gland of the left kidney, and the child was referred to our clinic. After conducting MSCT of the abdominal cavity, a differential series was established between a spleen cyst and a duplication of the stomach. On control ultrasound, negative dynamics in size were subsequently revealed. Indications for surgical treatment were established. Histologically confirmed the variant of duplication of the stomach. Conclusion: The multimodal approach allows timely diagnosis of the presented pathology, differential diagnosis of stomach duplication with rare localization and determination of indications for surgical treatment.
Keywords: Gastric duplication, children, surgical treatment.